Molecular Dynamics Simulation on the Wettability of Nanoscale Wrinkles High Water Adhesion of Rose Petals - Shao, Jinwei (Langmuir : the ACS journal of surfaces and colloids, 2022)
Understanding the high water adhesion of rose petals is of great significance in artificial surface design. With all-atom molecular dynamics simulation, the wettability of nanoscale wrinkles was explored and compared to that of nanoscale strips with favorable hydrophobicity. The dewetting and wetting of gaps between nanoscale structures represent the Cassie-Baxter (CB) and Wenzel (WZ) states of the macroscopic droplet deposited on the textured surface, respectively. We uncovered the intermediate state, which is different from the CB and WZ states for wrinkles. Structures and free-energy profiles of metastable and transition states under various pressures were also investigated. Moreover, free-energy barriers for the (de)wetting transitions were quantified. On this basis, the roles of pressure and the unique structures of nanoscale wrinkles in the high water adhesion of rose petals were identified